The family creative workshop : enamelling metal fantasy flowers framing fur re-cycling gingerbread glass working gold leafing granny swuares hammocks and slings hardanger embroidery heraldry herbs - Foy, Sally (Plenary Publications International, 1976)
128 p. : il.; 27 cm.